ADVANCED SEISMIC RESERVOIR CHARACTERIZATION OF ANGSI FIELD, MALAY BASIN, USING STOCHASTIC INVERSION AND SQP-SQS TRANSFORMATION - SAFIRA, NINE (2024)
This research addresses the limitations of deterministic methods in reservoir characterization, which often fail to accurately represent complex geological structures due to their lack of linearity and uniqueness.